2018
DOI: 10.1093/schbul/sby016.479
|View full text |Cite
|
Sign up to set email alerts
|

T203. Illicit Drugs Use and Ultra-High Risk (Uhr) for Psychosis Status in a Latin-American Sample

Abstract: BackgroundIn recent years, a number of investigations have evaluated the effect of cannabis use on the risk of presenting ultra-high risk for psychosis (UHR) status as well as its influences on transition rate, suggesting a dose-dependent interaction. On the other hand, the association between cocaine (snorted or smoked) - an increasing health issue in several countries worldwide - and the UHR state was not appropriately examined. Also, exposure to other psychotomimetic drugs, as amphetamines and lysergic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Of the 10 studies in one meta-analysis (Marconi et al, 2016 ), none were from the Global South and of 36 studies in another review (Farris, Shakeel, & Addington, 2020 ) only one. This Brazilian study found cannabis use, especially earlier age of first use, to increase psychosis risk, but this study assessed prodromal symptoms and not psychosis (Serpa et al, 2018 ). Another study in Chile assessed the relative prevalence of schizophrenia in people treated for cannabis and cocaine use disorders, Although the study found the odds of having schizophrenia or other related disorders was almost five times greater among cannabis users than cocaine users it was unable to compare this to the odds of psychosis in the general population (Libuy, de Angel, Ibanez, Murray, & Mundt, 2018 ).…”
mentioning
confidence: 95%
“…Of the 10 studies in one meta-analysis (Marconi et al, 2016 ), none were from the Global South and of 36 studies in another review (Farris, Shakeel, & Addington, 2020 ) only one. This Brazilian study found cannabis use, especially earlier age of first use, to increase psychosis risk, but this study assessed prodromal symptoms and not psychosis (Serpa et al, 2018 ). Another study in Chile assessed the relative prevalence of schizophrenia in people treated for cannabis and cocaine use disorders, Although the study found the odds of having schizophrenia or other related disorders was almost five times greater among cannabis users than cocaine users it was unable to compare this to the odds of psychosis in the general population (Libuy, de Angel, Ibanez, Murray, & Mundt, 2018 ).…”
mentioning
confidence: 95%